2017
DOI: 10.1038/s41598-017-03292-w
|View full text |Cite
|
Sign up to set email alerts
|

The cannabinoid ligand LH-21 reduces anxiety and improves glucose handling in diet-induced obese pre-diabetic mice

Abstract: LH-21 is a triazol derivative that has been described as a low-permeant neutral CB1 antagonist, though its pharmacology is still unclear. It has been associated with anti-obesity actions in obese rats. However, its role in preventing type 2 diabetes (T2D) onset have not been studied yet. Given CB1 receptors remain as potential pharmacological targets to fight against obesity and T2D, we wanted to explore the metabolic impact of this compound in an animal model of obesity and pre-diabetes as well as the lack of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 38 publications
4
45
0
Order By: Relevance
“…There is a growing body of evidence suggesting that the endocannabinoid system has a role in the regulation of cell proliferation and apoptosis . We have previously reported that CB1 and CB2 agonists protect mouse islets from apoptosis, and we recently demonstrated that LH‐21 delivery to pre‐diabetic mice has anti‐inflammatory and cytoprotective effects . In the present study we showed that LH‐21 has direct anti‐apoptotic effects in isolated human and mouse islets and the use of islets from GPR55 −/− mice indicated that, as for stimulation of insulin secretion and [Ca 2+ ] i , this was GPR55‐mediated.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…There is a growing body of evidence suggesting that the endocannabinoid system has a role in the regulation of cell proliferation and apoptosis . We have previously reported that CB1 and CB2 agonists protect mouse islets from apoptosis, and we recently demonstrated that LH‐21 delivery to pre‐diabetic mice has anti‐inflammatory and cytoprotective effects . In the present study we showed that LH‐21 has direct anti‐apoptotic effects in isolated human and mouse islets and the use of islets from GPR55 −/− mice indicated that, as for stimulation of insulin secretion and [Ca 2+ ] i , this was GPR55‐mediated.…”
Section: Discussionsupporting
confidence: 51%
“…Since LH‐21, an inverse agonist/neutral antagonist of CB1, shows structural similarities with AM251 and rimonabant, we investigated whether its activation of islet GPR55 could underlie at least some of its reported positive effects on glucose management . An earlier study used a static incubation protocol to show that the CB1 antagonists AM251 and JD‐5037 increased insulin release from human islets, and in the present study we employed perifusion experiments to demonstrate that LH‐21 also promoted insulin secretion from human islets.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…CID16020046 has extended the association of GPR55 to cancer, blocking LPI-evoked angiogenesis in ovarian carcinoma and migration of breast cancer cells [24,25]. Treatment of mice with CID16020046 counteracted the anxiogenic and other behavioural effects of the cannabinoid ligand LH-21, which had previously been suggested to act via GPR55 and independently of cannabinoid CB 1 receptor [26]. Antagonists have also been used to confirm affinity for GPR55 of newly recognised lipid agonists, including LPC (lysophosphaditylcholine) and N-arachidonoylglycine [27][28][29].…”
Section: Introductionmentioning
confidence: 99%